Investigation of the metaphysics of the light in the Illumination philosophy - محمود صیدی; hasan Akhtar (حکمت اسرا, 2014)
Illumination is the point at which the first Spydە morning sun appears to rise degrading light and knowledge. The result of the manifestation of the wisdom of illumination lights of reason on the basis of its population on the basis of light and topics related to it.The light and its degrees are the base of Illumination philosophy. Suhravardi is the first one who by inspiration of antique philosophers of Persian and Greece tried to found it. In spite of the Suhravardi”s endeavors in explaining and explicating Illumination philosophy, some of his views in this regard are not true and some other ones has implications and sequences that he hasn’t analyzed them. In this article, the author has tried to review Illumination philosophy in the regard of the Light and to prove that principle of this philosophy will explain and demonstrate some of philosophical problems that Peripatetic can’t not explicate them. Key Words: Suhravardi, Light, Nura- Al Anwar, Qavahir, Intuition, Illumination